33.0k views
2 votes
Rearrange the equation so n is the independent variable M+1=-2(n+6)

2 Answers

2 votes

Answer:

The answer is M = -2n - 13

Explanation:

m+1=−2(n+6) First, multiply the number outside the parentheses.

m+1 = -2n -12 Then, subtract the one from m to get the m isolated.

m = -2n - 13 is your answer!

User Miniwark
by
5.6k points
3 votes

Answer:

-1/2(M + 13) = n

Explanation:

To make n the independent variable, solve for n using inverse operations.

M + 1 = -2(n + 6)

M + 1 = -2n -12

M + 1 +12 = -2n

M + 13 = -2n

-1/2(M + 13) = n

User Evana
by
5.7k points